Model for pressure drop and flow deflection in the numerical simulation of stents in aneurysms. (29th January 2018) - Li, Sha; Latt, Jonas; Chopard, Bastien
Abstract: The numerical simulation of flow diverters like stents contributes to the development and improvement of endovascular stenting procedures, leading ultimately to an improved treatment of intracranial aneurysms. Due to the scale difference between the struts of flow diverters and the full artery, it is common to avoid fully resolved simulations at the level of the stent porosity. Instead, the effect of stents on the flow is represented by a heuristic continuum model. However, the commonly used porous media models describe the properties of flow diverters only partially, because they do not explicitly account for the deflection of the flow direction by the stent. We show that this deficiency can be circumvented by adopting the theoretical framework of screen models. The article first reviews existing screen models. It then proposes an explicit formula for the drag and the deflection coefficient, as predicted by each model, for both perpendicular and inclined angles. The results of 2D numerical simulations are used to formulate a generalization of these formulas, to achieve best results in the case of stent modeling. The obtained model is then validated, again through 2D numerical simulation. Abstract : We develop an effective model that can properly represent, at continuum scale, a stent in an aneurysm. Compared with the approach adopted by previous authors in the literature, the porous medium method, we take into consideration the deflection effect caused by the stent. The article reviews existing screen models for the drag and the deflection coefficient. A novel idea is presented for applying the obtained model to stent modeling. The model is then validated through 2D numerical simulation.